2011
DOI: 10.1111/j.1399-6576.2011.02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate limitation and cardiac unloading in sevoflurane post‐conditioning

Abstract: SePost (1.5-3%) reduced infarct size after regional myocardial ischemia in vivo and reduced cardiac work was significantly correlated to myocardial salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…ischemia-reperfusion (I/R) injury, is also initiated 1 . The volatile anesthetic sevoflurane emerged as an important cardioprotective agent in I/R injury of rats, mice 2 , rabbits 3 , pigs 4 and in coronary artery disease 5 of human beings. Sevoflurane produces anesthesia of excellent quality, possesses little systemic toxicity, and undergoes limited biotransformation 6 .…”
mentioning
confidence: 99%
“…ischemia-reperfusion (I/R) injury, is also initiated 1 . The volatile anesthetic sevoflurane emerged as an important cardioprotective agent in I/R injury of rats, mice 2 , rabbits 3 , pigs 4 and in coronary artery disease 5 of human beings. Sevoflurane produces anesthesia of excellent quality, possesses little systemic toxicity, and undergoes limited biotransformation 6 .…”
mentioning
confidence: 99%
“…Reimer and Jennings [ 26 ] were also able to achieve an improvement in myocardium salvage through the administration of propranolol in dogs after circumflex coronary artery ligation. More than three decades later the paradigm “slow the heart rate to preserve myocardium viability” has remained valid, as showed by recent studies in which the administration of drugs able to reduce heart rate and oxygen consumption were able to improve myocardial salvage in animal models of reperfused myocardial infarction [ 6 , 27 ]. Heart rate reduction by Ivabradine appears to have a positive effect on coronary collateral function in patients with chronic stable coronary artery disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to better understand the determinants of progression of necrotic wave [ 1 ] to develop new reperfusion strategies able to maximize the salvaged area and improve clinical parameters and prognosis [ 2 , 3 ]. In last year's, several studies have been carried out in animals demonstrating that higher heart rates during the acute phase of STEMI were associated with larger myocardial damage, regardless of the time of coronary occlusion [ 4 , 5 , 6 ]. Nevertheless, still there is a lack of evidence in humans, since for a long time, histological examination has been the only existing technique to quantify the amount of salvaged myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…This medication quickly enters blood through lungs and leaves blood with the same speed, therefore has a rapid anesthesia and anesthesia return. Minimum alveolar concentration (MAC) is 4.1% in elderly and 3.3% in children (Larsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Rivenes et al (2001) found out that halothane causes a significant reduction in the average pressure of ejection fraction and the heart index. Moreover, in a study done by Larsen et al (2012) it became evident that Sevoflurane reduces regional area of infarction and improves hemodynamics in patients. Findings of a research conducted by Hasani et al (2011) (Hasani et al, 2013) indicated that compared with propofol, sevoflurane could have similar and safe effects in non-relaxant intubation in children undergoing surgery (Moshiri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%